2004
DOI: 10.3748/wjg.v10.i6.856
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-starch polysaccharides enzymes on pancreatic and small intestinal digestive enzyme activities in piglet fed diets containing high amounts of barley

Abstract: AIM:To investigate effects of non-starch polysaccharides(NSP) enzymes on pancreatic and small intestinal digestive enzyme activities in piglet fed diets containing high amounts of barley. METHODS:Sixty crossbred piglets averaging 13.5 kg were randomly assigned to two treatment groups with three replications (pens) based on sex and mass. Each group was fed on the diet based on barley with or without added NSP enzymes (0.15%) for a 40-d period. At the end of the experiment the pigs were weighed. Three piglets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…There was no significant effect (P>0.05) of the supplementation with xylanase on the activities of brush-border enzymes (Table 2). These results agree, in part, with those by Li et al (2004) who Differences compared to the control diet within rows are marked † for tendencies (P≤0.10) 2 leucine aminopeptidase reported that the supplementation of pig diets based on barley with both xylanase and β-glucanase caused a significant increase in activity of γ-glutamyl transpeptidase in the jejunal mucosa only, whereas activities of disaccharidases, including maltase and lactase, were not significantly changed. Moreover, the authors showed that exogenous non starch polysaccharides (NSP) degrading enzymes decreased significantly activities of pancreatic enzymes, including α-amylase and lipase, in digesta obtained from the distal part of the duodenum.…”
Section: Resultssupporting
confidence: 81%
“…There was no significant effect (P>0.05) of the supplementation with xylanase on the activities of brush-border enzymes (Table 2). These results agree, in part, with those by Li et al (2004) who Differences compared to the control diet within rows are marked † for tendencies (P≤0.10) 2 leucine aminopeptidase reported that the supplementation of pig diets based on barley with both xylanase and β-glucanase caused a significant increase in activity of γ-glutamyl transpeptidase in the jejunal mucosa only, whereas activities of disaccharidases, including maltase and lactase, were not significantly changed. Moreover, the authors showed that exogenous non starch polysaccharides (NSP) degrading enzymes decreased significantly activities of pancreatic enzymes, including α-amylase and lipase, in digesta obtained from the distal part of the duodenum.…”
Section: Resultssupporting
confidence: 81%
“…These results reflect the fact that water-soluble NSP of wheat and barley impede pancreatic α-amylase and lipase activities (Li et al, 2004). This mode may indicate needs for greater secretion of pancreatic enzymes (Williams, 1996;Denbow, 2000).…”
Section: Effect Of Non-starch Polysaccharide (Nsp) Of Wheat and Barlementioning
confidence: 99%
“…This mode may indicate needs for greater secretion of pancreatic enzymes (Williams, 1996;Denbow, 2000). Based on relevant research findings intestinal enzyme activity depends on the original of dietary nutrient and quantity or quality of anti-nutrients in the gut (Li et al, 2004;Mirzaie et al, 2012). Also diet issue affects the magnitude of secretion…”
Section: Effect Of Non-starch Polysaccharide (Nsp) Of Wheat and Barlementioning
confidence: 99%
See 1 more Smart Citation
“…The most of the studies focuses on the use of exogenous NSP enzymes in diets for weaned piglets, as especially piglets do not produce enzymes capable of degrading NSP (Kerr & Shurson 2013). Li et al (2004) and Fan et al (2009) reported that the addition of b-glucanase and xylanase to barley-based diets improved growth performance of piglets. However, the need for exogenous NSP enzyme supplementation of barley-based diets on weaned piglets can depend on the used barley variety (Prandini et al 2014).…”
Section: Discussionmentioning
confidence: 99%